Domestication and Foreignization Strategies in Translating Islamic Culture-Bound Terms: A Case Study of Assalamualaikum Baitullah - Maulida Hayati Kresnadi; Dedi Sulaeman; Erlan Aditya Ardiansyah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigates the translation of Islamic culture-bound terms in the English subtitles of the film Assalamualaikum Baitullah. Unlike previous studies that have largely focused on secular culture-specific expressions in mainstream films, this research addresses a gap in the literature by examining the translation of Islamic religious terminology in an Indonesian cinematic context. Drawing on Venuti’s (2008) framework of domestication and foreignization, the study explores how culturally and theologically significant Islamic terms are rendered for English-speaking audiences. Using a descriptive qualitative approach, the research analyzes 43 Islamic culture-bound terms identified from the film’s Indonesian dialogue and their corresponding English subtitles. The findings indicate that domestication is the predominant strategy, accounting for 79.07% of the data, while foreignization represents 20.93%. Domestication is primarily employed to enhance comprehensibility and ensure a natural reading experience by translating religious expressions into culturally familiar English equivalents. In contrast, foreignization is used selectively for terms that carry distinctive Islamic meanings and lack adequate equivalents in English, thereby preserving their religious authenticity and cultural significance. Overall, the findings reveal the translator’s effort to balance audience accessibility with the preservation of Islamic cultural identity, contributing valuable insights to the field of audiovisual translation and the localization of religious content.